2012
DOI: 10.2172/1113766
|View full text |Cite
|
Sign up to set email alerts
|

Alstom's Chemical Looping Combustion Prototype for CO<sub>2</sub> Capture from Existing Pulverized Coal-Fired Power Plants

Abstract: Alstom's Limestone Chemical Looping (LCL™) process has the potential to capture CO 2 from new and existing coal-fired power plants while maintaining high plant power generation efficiency. This new power plant concept is based on a hybrid combustiongasification process utilizing high temperature chemical and thermal looping technology. This process could also be potentially configured as a hybrid combustion-gasification process producing a syngas or hydrogen for various applications while also producing a sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A calcium-based oxygen carrier, CaSO 4 , has been attractive as a potential oxygen carrier for CLC of solid fuels. Alstom Power Co. Ltd. , proposed its hybrid combustion–gasification chemical looping system. Wang and Anthony also proposed a CO 2 -based gasification-coupled chemical looping process for the clean fuel combustion with the CaSO 4 oxygen carrier.…”
Section: Introductionmentioning
confidence: 99%
“…A calcium-based oxygen carrier, CaSO 4 , has been attractive as a potential oxygen carrier for CLC of solid fuels. Alstom Power Co. Ltd. , proposed its hybrid combustion–gasification chemical looping system. Wang and Anthony also proposed a CO 2 -based gasification-coupled chemical looping process for the clean fuel combustion with the CaSO 4 oxygen carrier.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Lyngfelt et al designed a CLC unit and built a test platform, which marked the development of CLC technology from theoretical analysis to experimental study. Then, the first operation using solid fuel in a 10 kW CLC unit was demonstrated, and subsequently, a large number CLC pilot plants were constructed and operated, such as the 10 kW th and 100 kW th units at Chalmers University of Technology, the 50 kW th unit at Instituto de Carboquímica–Consejo Superior de Investigaciones Cientifícas (ICB–CSIC), the 25 kW th unit at The Ohio State University, the 10 kW th unit at Tsinghua University, the 10 kW th unit at IFP Énergies nouvelles, the 10 kW th and 50 kW th units at Southeast University, the 50 kW th unit at Huazhong University of Science and Technology, the 200 kW th unit at the University of Utah, the 1 MW th unit at Darmstadt University of Technology, and the 3 MW th unit of Alstom USA, etc. The autothermal operation of CLC is still a big challenge .…”
Section: Introductionmentioning
confidence: 99%
“…potential to be the lowest-costc ommercial technology for simultaneous energy productiona nd CO 2 separation. [2][3][4] Researchers at GE-Alstom have reported [2,3] that CLC and gasification are the two lowest-cost technologies in aC O 2 -constrained world.W ork at NETL [4] has shown that the CLCofnatural gas has alower cost than conventional natural gas combustion with CO 2 control but that carrier durability is apotential issue.…”
Section: Introductionmentioning
confidence: 99%